The Impact of the Jigsaw Cooperative Learning Approach on Students' Achievement in Islamic Education and Character-Building Subjects - Istihawa, Fidenia; Maksum, Ali; Umihani, Umihani (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aims to analyze the learning outcomes of Islamic Education before and after applying the Jigsaw cooperative learning method and to evaluate its impact on improving students' academic achievement in Islamic Education subjects. The research specifically investigates the influence of the Jigsaw learning approach on student achievement in an experimental study conducted in Grade XI at SMAN 3 Pandeglang. The study employed a quasi-experimental design involving two groups: an experimental group and a control group. A quantitative research approach was used, utilizing a survey method. The sampling technique employed was simple random sampling, selecting 69 students as the sample based on the nonequivalent formula. Data were collected through test distribution. After implementing the Jigsaw approach, the findings indicate a significant improvement in students' academic achievement in Islamic Education and character-building subjects. The pretest mean score of the experimental group was 64.43, which increased to 69.35 in the posttest. Similarly, students' performance in the control group improved from a pretest score of 65.93 to a posttest score of 71.80. Hypothesis testing using the t-test revealed a t-value (t = 10.82) greater than the critical value (t = 2.03) at a 5% significance level, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). Thus, the Jigsaw cooperative learning approach impacts students' academic achievement. In contrast, conventional methods show no significant effect on the learning outcomes of Islamic Education and Character Building in Grade XI at SMAN 3 Pandeglang.